The mitigating effects of maternal social support and paternal involvement on the intergenerational transmission of violence. (April 2018) - Tracy, Melissa; Salo, Madeleine; Appleton, Allison A.
Abstract: Childhood maltreatment is a strong risk factor for subsequent violence, including violent behaviors in young adulthood and offspring maltreatment after becoming a parent. Little is known about the specific circumstances under which supportive relationships may help disrupt this cycle of violence throughout the life course. We conducted two complementary analyses to assess whether maternal social support in early childhood, and also paternal involvement in middle childhood, could prevent the intergenerational transmission of violence, using data from the Avon Longitudinal Study of Parents and Children (n = 11, 384). We found that higher levels of maternal social support in the postpartum period reduced the odds of offspring maltreatment at ages 0–8 years (OR = 0.95, 95% CI 0.93–0.96). When classifying mothers according to their abuse history, this protective association of social support was observed among mothers with no history of childhood maltreatment and among those with only childhood maltreatment (and not postpartum intimate partner violence [IPV]), but not among mothers who reported IPV since the child's birth. We then extended our analysis of these offspring forward in time and found that paternal involvement at ages 9–10 years was associated with a reduced risk of offspring self-reported violent perpetration at ages 18–20 years (OR = 0.85, 95% CI = 0.77–0.94). This protective association was generally apparent among all subgroups of children, including those with a history of childhood maltreatment. Together these results highlight the protective influence of supportive relationships against the intergenerational transmission of violence, depending on abuse history, context, and timing, with important implications for the prevention of childhood maltreatment and mitigation of its negative effects.